Ontological and epistemological commitments in interdisciplinary water research: Uncertainty as an entry point for reflexion - Krueger, Tobias; Alba, Rossella (Frontiers in Water, 2022)
Against the background of a renewed interest in interdisciplinary water research, we begin this paper by diagnosing a need for deeper engagement at the epistemological and ontological level. We then analyse the ontological and epistemological commitments of three modeling examples: an academic human-flood model, a nutrient transfer decision support model and a policy facing water security model. These examples demonstrate how research practices are not neutral but intervene in the world by distributing agency unequally, providing naturalized and de-politicized explanations of the past and pre-configuring certain futures while foreclosing others. Lastly, we position hydrology's uncertainty tradition and its problematisation of choices in the research process as an entry point for reflexion on the contingencies of and ethical responsibility for research practices. This uncertainty tradition provides more common ground for collaboration between hydrologists and critical water researchers than previously acknowledged, while such collaboration would still thrive on confrontation. We conclude with a call for greater humility in water research, especially when using models, and practical suggestions for how researchers could uncover ontological and epistemological commitments and live up to the ethical responsibility they entail.